The bird species composition of the nature reserve and historical Vinh Cuu, Dong Nai province - Tuong, Ngo Xuan; Thuy, Le Dinh; Quynh, Ha Quy (Academia Journal of Biology, 2014)
The bird species composition of the nature reserve and historical Vinh Cuu, Dong Nai province